2013
DOI: 10.1080/02640414.2013.807351
|View full text |Cite
|
Sign up to set email alerts
|

Variants within theCOMPandTHBS2genes are not associated with Achilles tendinopathy in a case-control study of South African and Australian populations

Abstract: Cartilage oligomeric matrix protein is a structural protein of the extracellular matrix, while thrombospondin-2 is a matricellular protein involved in cell-matrix interactions. Recent studies have shown that genetic variation is a significant risk factor for Achilles tendinopathy, and the genes encoding cartilage oligomeric matrix protein (COMP) and thrombospondin-2 (THBS2) were identified as good candidate genes for association with Achilles tendinopathy. This study aimed to test the association of sequence v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…46,61,155 The relationship between genotype, abnormal collagen, mechanical stress, and symptom presentation is multifactorial and not well understood. 11,72,156,163,172…”
Section: Pathoanatomical Features 2018 Summary and Updatementioning
confidence: 99%
“…46,61,155 The relationship between genotype, abnormal collagen, mechanical stress, and symptom presentation is multifactorial and not well understood. 11,72,156,163,172…”
Section: Pathoanatomical Features 2018 Summary and Updatementioning
confidence: 99%
“…In recent years, several tendinopathy candidate genes have been investigated resulting in the successful identification of genetic variants that contribute to risk with moderate to large effect sizes 2 7 . Several other studies have found no association between the candidate variants investigated and the condition 10 11 12 13 . However, it is worth noting that using this approach, the lack of association with a candidate variant does not exclude other variants within that gene as contributors to tendinopathy risk.…”
mentioning
confidence: 70%
“…Both proteins are believed to be involved in cell-to-cell adhesion and communication. 20 , 80 Saunders et al 69 investigated the COMP and THBS2 genes in 178 Achilles tendinopathy and 340 control patients. They failed to find any significant differences in genotype distributions for the COMP variants rs730079 ( P = .73) and rs28494505 ( P = .99) or for the THBS2 variants rs9505888 ( P = .24), rs6422747 ( P = .65), and rs 9283850 ( P = .60).…”
Section: Resultsmentioning
confidence: 99%